2015
DOI: 10.1113/jp270743
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate cycling may drive organic anion transport on the basal membrane of human placental syncytiotrophoblast

Abstract: Key points The placenta removes waste products, drugs and environmental toxins from the fetal circulation and two of the transport proteins responsible for this are OAT4 and OATP2B1 localised to the basal membrane of placental syncytiotrophoblast.We provide evidence that OAT4 and OATP2B1 mediate glutamate efflux when expressed in Xenopus oocytes and that in the perfused placenta, bromosulphothalein (an OAT4 and OATP2B1 substrate) stimulates glutamate efflux.Furthermore the efflux of glutamate can only be seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Like OAT4, this transporter is involved in the transport of estrone sulfate and dehydroepiandrosterone sulfate, and this process may be sodium dependent [62]. It has also been proposed that the transport of glutamate may also be coupled to anion transport by both OATP2B1 and OAT4, though this may need to be studied with more substrates [63]. OATP4A1, on the other hand, is expressed on the apical membrane of the syncytiotrophoblast [58,61].…”
Section: Mechanisms Of Drug Transport Across the Placentamentioning
confidence: 99%
“…Like OAT4, this transporter is involved in the transport of estrone sulfate and dehydroepiandrosterone sulfate, and this process may be sodium dependent [62]. It has also been proposed that the transport of glutamate may also be coupled to anion transport by both OATP2B1 and OAT4, though this may need to be studied with more substrates [63]. OATP4A1, on the other hand, is expressed on the apical membrane of the syncytiotrophoblast [58,61].…”
Section: Mechanisms Of Drug Transport Across the Placentamentioning
confidence: 99%
“…Recent studies in human placenta have also demonstrated a role for glutamate as a counter‐ion to mediate placental uptake of xenobiotics and hormones from fetal circulation (Lofthouse et al . , ).…”
Section: Introductionmentioning
confidence: 99%
“…Placental uptake of glutamate from maternal and fetal blood is mediated by system X AG-. Recent studies in human placenta have also demonstrated a role for glutamate as a counter-ion to mediate placental uptake of xenobiotics and hormones from fetal circulation (Lofthouse et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Placental amino acid transfer, must be thought of as a system rather than simply focusing on individual mechanisms (Lofthouse et al . ). A computational modelling approach is helping us to predict the rate‐limiting factors in this system so that these can be the focus of future intervention‐based studies (Panitchob et al .…”
Section: Introductionmentioning
confidence: 97%
“…Placental perfusions provide the best system for modelling transfer and the combination of perfusions with modelling has provided unexpected insight into placental amino acid, fatty acid and cortisol transport (Lofthouse et al . ; Panitchob et al . ; Perazzolo et al .…”
Section: Introductionmentioning
confidence: 99%